Juridical Analysis Of Actions And Legal Consequences For Corporations Involved In Corruption - Yudiansyah B; Yasmirah Mandasari Saragih; Syaiful Asmi (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2024)
The purpose of writing this journal is to identify and analyze the ways and motives behind corrupt acts carried out by corporations, as well as understand the organizational structure and market dynamics that influence these corrupt practices. And evaluate the legal consequences that apply to corporations involved in acts of corruption and examine the effectiveness of implementing these penalties in efforts to prevent and overcome corruption among corporations. The approach method used in this research is Normative Law (normative juridical) using a statutory approach, a conceptual approach, and a comparative and empirical approach (field data). The research results show that corporations are involved in acts of corruption through various, often complex and covert means, driven by motives to increase profits, dominate markets, or avoid regulations. The mechanisms they use range from giving bribes, manipulating tenders, to money laundering practices. Corporations involved in acts of corruption can face a number of legal consequences, ranging from heavy fines, license revocation, asset confiscation, to operational restrictions. Although these penalties are intended to provide a deterrent effect, their effectiveness in preventing corporate corruption often varies. While fines may have a financial impact, without significant internal changes in corporate culture and governance, the potential for a return to corrupt behavior remains.